A new species of sea anemone from the Chilean fjord region, Paraisanthus fabiani (Actiniaria: Isanthidae), with a discussion of the family Isanthidae Carlgren, 1938 - Häussermann, Verena; Försterra, Günter (Zootaxa, 2008)
A new species of Paraisanthus, P. fabiani, is described from Chile, the eighth species of this small family of mesomyarian anemones. Specimens of this species are characterized by six pairs of macrocnemes and 18 pairs of microcnemes in the middle and lower column and a fourth incomplete cycle of extremely small mesenteries in the uppermost column, between 66 and 110 tentacles, and a smooth column without holotrichs or heterotrichs. Specimens occur from the shallow subtidal to at least 30 m around exposed islands and in less protected channels of the fjord region between Chiloé Island (41°7’04.8’’S; 73°53’02.4’’W) and the Madre de Dios Archipelago (50°20’23.1’’S; 75°22’39.2’’W). They often protrude from small rocky crevices or between polychaete tubes, so that in situ only the oral disc is visible. The description is based on examination of 27 specimens collected between 1997 and 2007 and on documentation of live specimens in both their natural environment and aquaria. Paraisanthus fabiani was found at only 15 of over 150 study sites along the Chilean coast. If it was present at a site, generally more than 10 specimens were found. For the first time, in situ photographs are provided for a member of the family Isanthidae. In addition, live photographs are provided for the type species of the family Isanthidae, Isanthus capensis from South Africa. Family Isanthidae constitutes five genera, which are distinguished mainly by number of macrocnemes, texture and division of the column, and direction of growth of mesenteries.